The optimal true ileal digestible lysine and total sulfur amino acid requirement for nursery pigs between 20 and 50 lb - J D Schneider; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2005)
An experiment involving 360 pigs (PIC, avg. BW = 22.0 lb) was conducted to determine the appropriate true ileal digestible (TID) lysine and total sulfur amino acid (TSAA) requirement of nursery pigs and, consequently, to determine the optimal TSAA:lysine ratio. This trial was organized as a combination of two simultaneous experiments, with one set of diets consisting of five increasing TID lysine concentrations (1.05, 1.15, 1.25, 1.35, and 1.45%) and the second set of diets consisting of five increasing TID TSAA concentrations (0.61, 0.69, 0.76, 0.83, and 0.90%). The highest concentrations of both lysine and TSAA (1.45% and 0.90%, respectively) were combined as one diet and used in both the lysine and TSAA titrations, to give a total of 10 treatments. Pigs were randomly allotted to eight replications, with five pigs per pen, on the basis of initial BW. Average daily gain and F/G improved (quadratic, P<0.01) with increasing TID lysine. The largest improvement in growth rate and feed efficiency for PIC pigs in these facilities occurred as the TID lysine increased to 1.25 and 1.35%, respectively; there was little improvement in performance thereafter. Increasing TID TSAA increased (quadratic, P<0.01) ADG and improved (quadratic, P<0.01) F/G, although the largest increases in ADG and F/G occurred as TID TSAA increased from 0.61 to 0.76%, with smaller improvements from 0.76 to 0.90%. Average daily gain and F/G values were plotted as the dependent variables in a regression analysis, with the TID lysine and TSAA concentrations on the Y axis. Regression analysis of the response surface resulted in an estimated TID TSAA-to-lysine ratio range of approximately 55 to 56% for optimal ADG and F/G.; Swine Day, 2005, Kansas State University, Manhattan, KS, 2005
Keywords: Swine day; 2005; Summary Publication of Report of Progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 964; Kansas Agricultural Experiment Station contribution; no. 06-63-S; Lysine; TSAA; Nursery pig; Swine